FIRST BATCH OF USM-KLE GRADUATED DOCTORS ARE OF INTERNATIONAL STANDARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
BELGAUM, INDIA, 26 June 2015 – The pioneer batch of graduates from the Universiti Sains Malaysia (USM) - Karnataka Lingayat Education (KLE), India International Medical Programme will consist of 48 medical doctors of international standard who possess greater maturity due to their international exposure.